Comparison of Surgical Outcomes with Time Interval of Operation among extradural haematoma (EDH) Patients (Journal of National Institute of Neurosciences Bangladesh, 2018)
Background: Post-operative outcome of extradural haematoma (EDH) patients depends on the time interval of operation.Objectives: The purpose of the present study was to evaluate the role of time interval and surgical intervention in EDH.Methodology: This interventional study was carried out in the Department of Neurosurgery at Dhaka Medical College and Hospital, Dhaka, Bangladesh from July 2001 to July 2003 for a period of two (02) years. Patients with the history of head trauma admitted in Neurosurgery unit of Dhaka Medical College and Hospital which were being diagnosed as EDH both clinically and radiologically were included as study population. All patients were treated surgically and haematoma was evacuated. Outcome regarding neurological status, functional recovery, associated morbidity and mortality were assessed in each case as per Glasgow Outcome Scale and was compared between the two groups of patients who were treated surgically within 3rd day and 4th to 7th day after infliction of injury. The study population was devided into 4 groups on the basis of the consciousness level on admission of the patients. The EDH patietns who had GCS